Down regulation of estrogen receptors (ER; ER) and atypical chemokine receptors (ACKR 2; ACKR3; ACKR4) to increase 17β-estradiol (E2) levels in MCF-7 in-vitro study - Shruti Talashi (Basic & Clinical Cancer Research)
Background: Oestrogen plays a vital role in breast development and is strongly related to breast cancer. This research article delves into this paradox. Inflammation is a cancer hallmark that involve chemokine that attract inflammatory immune cells and promote breast cancer spread. E2 as a potential oestrogen can inhibit chemokine secretion, although the underlying mechanism remains unclear. Interestingly, atypical chemokine receptors (ACKRs), as anti-inflammatory G protein-independent transmembrane proteins, act as "scavengers," removing excessive chemokine's, resulting in reduced inflammation, and most strikingly, these genes are essential for normal breast development. This finding suggested that ACKRs may act as tumour suppressors. This study investigated whether a higher E2 level can influence the expression of its own receptors type and ACKRs.